Tindak Pidana Merintangi Penyidikan oleh Advokat pada Perkara Tindak Pidana Korupsi - Sahabuddin, S.; Hartono, M. Rudi; Manihuruk, Rospita (Wajah Hukum, 2025)
The profession of advocate or often known as a lawyer, attorney or legal advisor is a profession that is full of idealism because it holds a noble position (officium nobile) in fighting for justice and legal certainty and is able to provide free legal assistance to anyone who is unable to file a case. In the legal system, advocates have various functions, such as representing, accompanying, defending, and carrying out other legal actions on behalf of clients, as well as assisting the court in determining facts based on justice and exercising its authority. Advocates have rights and responsibilities in carrying out their duties. Complying with the Indonesian Advocate Code of Ethics and Law Number 18 of 2003 concerning Advocates is one of the rights and responsibilities of advocates. When defending a client, a lawyer must not violate applicable laws, moral standards, or the interests of others. However, in reality, some lawyers continue to engage in illicit activities, including criminal acts. obstructing the investigation in a corruption situation. The purpose of this study is to gather information. more in-depth about the criminal penalties imposed on advocates who obstruct investigations into alleged corruption, as well as the law enforcement procedures used to file charges against these individuals. The strategy used in this study is a case approach, while the method used is a type of normative legal research. Library data is the source of data in this study. The Corruption Court has conducted an examination process based on the findings of the investigation, and the District Attorney's Investigator in the jurisdiction where the legal event of obstruction of investigation occurred, has taken law enforcement actions against advocates who commit the crime of obstruction of investigation in corruption cases. The criminal provisions in Article 21 of Law of the Republic of Indonesia Number 31 of 1999 concerning the Eradication of Corruption as amended by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption, are the basis for criminalization for advocates who commit acts of obstructing investigations into corruption.